Effects of acetylated distarch phosphate on the physicochemical characteristics and stability of the oyster sauce system - Li, Xiao; Zou, Feixue; Kang, Xuemin; Gao, Wei; Cui, Bo; Sui, Jie (Frontiers in Nutrition, 2024)
The effect of acetylated distarch phosphate (ADSP) on texture, water state, interactions, microstructure and stability of oyster sauce (OS) were investigated. The results revealed that the firmness, consistency, cohesiveness, and water-holding capacity of OS were improved with the addition of ADSP. Moreover, ADSP reduced the average particle size, polydispersity index, and zeta potential of OS, indicating that electrostatic and steric stabilization existed in ADSP-OS system. The results of the Fourier-transform infrared spectroscopy and water state analysis verified that ADSP enhanced hydrogen bonding and decreased water mobility, respectively. Further, all ADSP-OS samples were typical non-Newtonian fluids with shear-thinning characteristics. In terms of microstructure, the OS containing ADSP had a more continuous and smooth structure, suggesting the dispersing and filling effects of starch.Nonsignificant instability index changes of ADSP-OS over the whole storage period confirmed the excellent long-term stabilization capability of OS prepared with ADSP .